Strategi Digital dan Desain-Pemasaran Startup Bisnis Manufaktur: Studi Kasus Panel Bambu Akustik Pemurni Udara - Bhaskara, Arkananta; Supriyati, Supriyati; Assidik, Fajar; Rizalulhaq, Muhammad; Rahmawati, Fani Annisa; Pharamitha, Pharadnya Dewi; Bahri, Ramadhan Syaeful (Labkat Press KA FTIK UNIKOM, 2024)
With the advancement of technology, startups, and small businesses are required to complete manual and inefficient work with advanced technology to achieve better performance. Work that is done manually must be further improved by using a computerized system. However, not all startups can utilize the development of information technology properly. This study aims to design a business development strategy for digitalization-based start-up companies in the fields of marketing and business strategy, with a focus on readiness to compete in the global market through online channels, as well as customer churn management to maintain loyalty and increase retention in the face of competitive market dynamics. The research method used is an experimental research method, with the unit of analysis on the startup of the Panel Bambu Akustik Pembersih Udara. The research data includes primary data from the company's sales reports and secondary data from scientific publications, journals, proceedings, and related regulations. The results of this study are in the form of a digital business strategy design that includes marketing design through the company's website, functioning as a business profile and transaction platform. This design is expected to guide companies in effectively accessing the global market. The implementation of the results of this study is expected to help manufacturing startups such as Air Purifying Acoustic Bamboo Panels compete in the international market through an integrated and effective online strategy. With the application, users can more easily spread product promotions and consumers can easily find out information about the product, from explanations to ordering.